Examining the Relationship between Superstitious Behavior in Sport and Trait Anxiety Levels among College Students Engaged in Active Sports - Utku Işık; Bülent Ağbuğa; Gürkan Elçi (ümit doğan üstün, 2015)
The purpose of this study was to examine the relationship between superstitious behavior in sport and trait anxiety levels among college students engaged in active sports. 166 Pamukkale University and Ege University of School of Physical Education and Sports students who are selected simple random sampling method voluntarily participated (61 females and 105 males) for the study. In the study for gathering data "Superstitious Ritual Questionnaire" and "Trait Anxiety Inventory" were used together. To examine the relationship between superstitious behavior in sport and trait anxiety levels the Pearson product-moment coefficients of correlation was used. The results indicated that the relationship between superstitious behavior in sport and trait anxiety level is positive and statistically significant (r=.208; p=.007). To explain whether there are significant differences between participants' superstitious behavior in sport according to gender, Independent Sample T-test was used. Result of this analysis revealed no statistically significant difference between male and female students tendency to superstitious behaviors according to gender (t=1.15; p=.251). In conclusion study findings showed that anxiety is a factor that increases university students, engaging in active sport, superstitions behavior.